PENGKAJIAN PENGEMBANGAN MODEL AGRIBISNIS JAGUNG PADA LAHAN KERING DI KABUPATEN CIAMIS - Saeful Bachrein (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Study on the Development of Maize Agribusiness Model in Up Land in Ciamis Regency. This study was conducted at Margaharja Village, Sub-district, Ciamis Regency from January to December, 2007. The objectives of the study were: (1) to design the formulation and development of agribusiness model system for village industry by implementing various technological and institutional innovations, and (2) to obtain feedback for the improvement of the model system and agribusiness activities as materials for program perfection. The activities were conducted by using